On Financing Global and International Public Goods - Sandler, Todd (World Bank, Washington, DC, 2014)
Three dimensions of public goods--nonrivalry of benefits, the possibility of being excluded from benefits, and the technology for aggregating public supply--determine what kinds of institutions and transnational actions are required for their provision and financing. For some public goods--especially for those for which the exclusion of nonpayers is not feasible--these properties are such that a public sector push is needed or the good will not be financed. This push can come from a supranational structure (such as the World Bank, the United Nations, or the European Union) that directly or indirectly collects the requisite fees from its members to underwrite international public goods (IPGs). To understand the role of international institutions in promoting IPGs, one must ascertain the nature of the good and whether it requires a push, a coax, or no assistance from a supranational structure or influential nation(s) and agents (such as charitable foundations). The transnational community should explicitly direct scarce resources only to those global and international public goods that need either a significant push or only a smaller coax by the transnational community. When clubs or markets can finance international public goods, the community should sit back and let incentives guide the actions of sovereign nations.